1989
DOI: 10.2337/diab.38.12.1643
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Endothelin Receptors and Effects of Endothelin on Diacylglycerol and Protein Kinase C in Retinal Capillary Pericytes

Abstract: Retinal capillary pericyte is a cell type selectively lost in early diabetic retinopathy. The physiological function of pericytes is not yet clearly identified, although it probably has contractile properties. We determined the specific binding of endothelin 1, a 21-amino acid peptide with potent vasoconstrictive action, and the stimulation of diacylglycerol/protein kinase C (DAG/PKC) pathway in cultured retinal capillary pericytes by endothelin. A single specific binding site for 125I-labeled endothelin was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Platelet-derived growth factor (PDGF) at submitogenic concentrations can enhance endothelin's mitogenic effect on smooth muscle cells (20). High-affinity receptors for endothelin have been identified in the murine cell line, 3T3, and in pericytes (21,22). Receptor binding leads to cellular proliferation, which can be inhibited by the calcium channel blockers (19).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-derived growth factor (PDGF) at submitogenic concentrations can enhance endothelin's mitogenic effect on smooth muscle cells (20). High-affinity receptors for endothelin have been identified in the murine cell line, 3T3, and in pericytes (21,22). Receptor binding leads to cellular proliferation, which can be inhibited by the calcium channel blockers (19).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that stimulated-as opposed to basal-phosphoinositide turnover, such as that involved in synaptic and trophic signal transduction, also is altered in diabetic peripheral nerve tissue is suggested by the following observation: Superior cervical ganglionic MI content, Na + -K + -ATPase activity, and muscarinic signal transduction are impaired by STZinduced diabetes in the rat, and are corrected by AR1 treatment (66,214), and total muscarinic agonist-stimulated PI turnover in human, retinal pigment epithelial cells (215) A variation of this polyol pathway-PKC model has been described in microvascular tissue, where glucose leads to increased de novo synthesis of DAG and PKC activation (216)(217)(218), which has been reported to be independent of polyol-related changes in Na + -K + -ATPase activity in cultured, retinal capillary endothelial cells (217). Provocative studies by the same authors suggesting that endothelin would potentiate the effects of glucose on DAG accumulation in retinal capillary pericytes and bovine aortic smooth muscle cells (219,220) have not been substantiated (221,222), however. Reconciliation of these observations with those described above for changes in DAG and PKC in nerve tissue (93,94,203,209,210) is problematic and may reflect tissuespecific differences.…”
Section: Phosphoinositide Metabolism and The Regulation Of Na + -K + mentioning
confidence: 90%
“…In vivo and in vitro studies have reported that various hormones and neuromodulators such as angiotensin II and vasopression affect the pericytes (Ferrari-Di et al, 1996;Matsugi et al, 1997;Rucker et al, 2000). In addition, endothelin-1, a vasoactive peptide, is also known to affect the function of pericytes as presence of endothelin receptors has been reported on them (Chakravarthy et al, 1992;Dehouck et al, 1997;Lee et al, 1989;Yamagishi et al, 1993). Pericytes not only make direct contact with the endothelial cells but also communicate with them through gap junctions (Allt and Lawrenson 2001;Diaz-Flores et al, 1991;Fujimoto, 1995;Sims, 1986).…”
Section: Pericytesmentioning
confidence: 95%